Outflows in the narrow-line region of bright Seyfert galaxies – I. GMOS-IFU data. Issue 2 (5th February 2018) - Freitas, I C; Riffel, R A; Storchi-Bergmann, T; Elvis, M; Robinson, A; Crenshaw, D M; Nagar, N M; Lena, D; Schmitt, H R; Kraemer, S B
Abstract: We present two-dimensional maps of emission-line fluxes and kinematics, as well as of the stellar kinematics of the central few kpc of five bright nearby Seyfert galaxies – Mrk 6, Mrk 79, Mrk 348, Mrk 607, and Mrk 1058 – obtained from observations with the Gemini Multi-Object Spectrograph Integral Field Unit on the Gemini North Telescope. The data cover the inner 3.5 arcsec × 5.0 arcsec – corresponding to physical scales in the range 0.6 × 0.9–1.5 × 2.2 kpc 2 – at a spatial resolution ranging from 110 to 280 pc with a spectral coverage of 4300–7100 Å and velocity resolution of ≈90 km s −1 . The gas excitation is Seyfert like everywhere but show excitation gradients that are correlated with the gas kinematics, reddening and/or the gas density. The gas kinematics show in all cases two components: a rotation one similar to that observed in the stellar velocity field, and an outflow component. In the case of Mrk607, the gas is counter-rotating relative to the stars. Enhanced gas velocity dispersion is observed in association with the outflows according to two patterns: at the locations of the highest outflow velocities along the ionization axis or perpendicularly to it in a strip centred at the nucleus that we attribute to an equatorial outflow. Bipolar outflows are observed in Mrk 348 and Mrk 79, while in Mrk 1058 only the blueshifted part is clearly observed, while in cases of Mrk 6 and Mrk 607, the geometry of the outflow needs further constraints from modelling to be presented in a forthcoming study, where the mass flow rate and powers will also be obtained.